The effectiveness of the DIC as a measurement system in SRG shear strengthened reinforced concrete beams - Funari, Marco Francesco (2021)
Steel Reinforced Grout (SRG) materials are generating considerable interest as strengthening system of reinforced concrete (RC) structures. They are finding increasing use in several civil engineering applications mainly due to the advantages they offer over traditional material such as high strength to weight ratio, ease of application, durability and low price. This paper describes the results of an experimental investigation carried out on SRG shear strengthened RC beams and gives evidence of the Digital Image Correlation (DIC) effectiveness as a measurement system. The tests performed had two main objectives: (i) assess the effectiveness of continuous and discontinuous U-wrapped jackets comprising a different number of layers and strips; (ii) assess the shear crack distribution during the tests by means of the DIC measurements. The results confirmed that reinforcing RC beams with SRG jackets can increase the load-bearing capacity; when the beam was reinforced with a continuous two-layered SRG strip, an increase of 84% was observed (compared to the unreinforced beam). The Linear Variable Differential Transformers (LVDT) measurements validated the results obtained by means of the DIC.